PRODUKSI DAN PEMASARAN PRODUK MANISAN PALA â€œILOMATAâ€ DI KELURAHAN GIRIAN WERU, KOTA BITUNG - Irene Pricilia Pangumpia; Lyndon R.J. Pangemanan; Nordy F.L. Waney (Sam Ratulangi University, 2016)
The purpose of this research is to describe the process of making candied nutmeg by UD Ilomata and describing Ilomata’s candied nutmeg marketing. The research carried out start from preparation in the April until preparation of reports in the June 2016. Data used is primary data obtained through interviews by giving questioners to the owner of UD Ilomata, and from direct observation to the production activity and marketing of Ilomata’s candied nutmeg. Data analysis used is descriptive analysis. Data analysis in this research is analysing market margin by calculating cost and the price margins on every channel marketing that involved in the marketing of Ilomata’s candied nutmeg and also calculate the Break Even Point. The result of this research shows that Ilomata’s candied nutmeg packed in three different packages, 3 ounce package, 2.5 ounce package, and 3 ounce package. Ilomata’s candied nutmeg marketed on four stores in Bitung City, two stores in Manado City, a store in Gorontalo province and the marketing directly from producer to the consumer in UD Ilomata. Biggest marketing margin is Rp 5.000 with 16% share found in the Gorontalo province’s channel marketing from the 2.5 ounce package and with the biggest profit margin is Rp 3.764 found in the Bitung CityMart’s channel marketing from the 2 ounce package. All of Ilotama’s channel marketing can be said efficient because total cost is small seen from the rotation of sold time product. UD Ilotmata’s Candied nutmeg business can hold on and exist till today because theres diligence, curiosity and entrepreneurship from the owner namely Mrs. Renny Umar.*lwths*